The inertisation of the zeolites ZSM-5, mordenite and beta by chemical vapour deposition using tetraethoxysilane - Weber, Reinier Willem; Weber, Reinier Willem (Department of Chemical Engineering, 2017)
The structural characteristic of greatest interest for catalysis in zeolites is the channel system, because these catalysts may display shape selective properties if the reactions take place within the channel system. However, the external surface of zeolites is accessible to all molecules and behaves in a non-shape selective manner. Coke formation on the external surface of zeolites may prevent access to the channel system of the zeolite due to pore blocking. It would thus be of great benefit to study the effects of inertising the external acidity of zeolites, thereby enhancing the shape selective properties of these catalysts, and possibly also to reduce coke formation at the entrances to the pores. Given the industrial importance of ZSM-5, this is a particularly good zeolite to study in this regard. Chemical vapour deposition (CVD) and chemical liquid deposition (CLD) methods have shown great promise in inertising the external surface acidity of zeolites and thus increasing their selectivity for various reactions. The external surface acidity can be inertised by a thin layer of silica coating the external surfaces of the zeolites. The silica layer can also narrow the pore openings uniformly, thus increasing the shape selective properties of the zeolites even more. By implication, coating ZSM-5 in a shell of iso-structural Silicalite-1 may provide an inert layer around the ZSM-5 crystals, without necessarily altering the pore opening size. In this study, the following methods have been used to inertise the external surface acidity of ZSM-5, Mordenite and Beta: (i) Chemical vapour deposition - Tetraethoxysilane (TEOS) was contacted with the catalyst using a vapour phase flow system and static vacuum system. The effects of deposition temperature and time were varied in order to vary the amount of TEOS deposited on the samples. The effect of the decomposition species formed during TEOS deposition on the complete inertisation of the external surface acidity was investigated. (ii) Chemical liquid deposition Pure tetraethoxysilane (TEOS) or tetraethoxysilane diluted in water, ethanol or n-hexane was contacted with the catalyst at ambient temperatures. The effect on the inertisation of the external surface acidity in the presence of diluents, similar in nature to typical decomposition products formed at certain different temperatures, was studied. (iii) Coating with Silicalite shells - Parent ZSM-5 seed crystals were immersed into a Silicalite-1 synthesis mixture in order to obtain an iso-structural coating. The seed crystals used for modification were (a) the assynthesized material, (b) detemplated but not ion-exchanged parent crystals (Na-form), and (c) detemplated and ion-exchanged parent crystals (NH4-form). The primary objective of these studies was to determine how. complete inertisation of the external surface acidity could be achieved. By modifying samples under different conditions as outlined above, information was obtained on the uniformity of the coating of samples modified in each of the different systems. ZSM-5, Mordenite and Beta samples modified using similar CVD and CLD modification conditions were compared. Post-modification treatment was employed to determine whether the silica layer deposited during CVD treatment was irreversibly attached to the external surface of the samples.